Assessment of SHCC overlay retrofitting of unreinforced load bearing masonry for seismic resistance - De Jager, Dirk Jacobus Adriaan (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.